KONTRIBUSI WANITA BEKERJA TERHADAP PENDAPATAN RUMAH TANGGA (Kasus Tenaga Kerja Wanita Pada PT.PSUT Sarang Burung Kec.Jambi Luar Kota) - Sudirman Sudirman; Ahmadi Ahmadi (Universitas Batanghari Jambi, 2013)
As a result of the loss of employment in the rural farming , also affect women as a component of rural households. In the end, the women find employment outside the sector agriculture in both rural and urban region . During this time that the concentration of development economists is more focused on the study of women workers who migrate to the city areas . However, in reality there are many women workers are still living in rural areas and engage in various economic activities .The involvement of women in economic activity and the activity at the same time stairs to do with changes in the economic structure , especially in rural areas is one of the interesting things that has not been revealed , especially women who are bound in the Company PT.PSUT Kec.Jambi Lauar City Bird's Nest . In this area to work in the industrial sector is one of the types of businesses that the majority of women do . The assessment was conducted to determine the extent of the involvement of women in the industry particularly with respect Palywood PT.PSUT involvement in the business reason , or is also one form of response to the structural changes that occur in the countryside .Keyword : Women working income, Sideline Income, Total Income